Al-Ghazali's Philosophical Theology and Its Relevance to the Polemic of Science and Islamic Theology During Pandemic Covid-19 - Fatkhan, Muh; Arif, Muhammad (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2023)
This article covers philosophical theology and its relevance to the issues between Islamic theology and science during Pandemic COVID-19. There were numerous scientific discoveries on covid-19 such as its contagion, the importance of physical distancing, the importance of wearing the mask, the importance of avoiding crowds, vaccines, etc. All of them have been public consumption. As a consequence, there was religious dissent in Muslim society. The one group took science on its side and negated any communal worship without health protocol. The other group chose “Islamic theology” and still conducted any communal worship without health protocol. To answer this reality, it is important to see how al-Ghazali handled philosophy and Islamic theology in harmony. Like al-Ghazali, Muslim society should respect scientific discoveries concerning the COVID-19 pandemic. However, not only appreciate the scientific discoveries but Muslim society also should keep in mind that the will and act of God are attached to the efforts of science to handle the COVID-19 pandemic.